2020
DOI: 10.3389/fcimb.2020.00206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Molecular Epidemiology, Clinical Characteristics, Antifungal Susceptibility Profiles, and Molecular Mechanisms of Antifungal Resistance of Iranian Candida parapsilosis Species Complex Blood Isolates

Abstract: Clonal expansion of fluconazole resistant (FLZ-R) Candida parapsilosis isolates is increasingly being identified in many countries, while there is no study exploring the antifungal susceptibility pattern, genetic diversity, and clinical information for Iranian C. parapsilosis blood isolates. Candida parapsilosis species complex blood isolates (n = 98) were recovered from nine hospitals located in three major cities, identified by MALDI-TOF MS, and their genetic relatedness was examined by AFLP fingerprinting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 72 publications
0
53
0
Order By: Relevance
“…Generally, changes in drug affinity at the drug target for azoles and echinocandins and overexpression of the drug target and efflux pumps are the major determinants of azole resistance. Considering that azoles are the main drug used to treat invasive candidiasis in developing countries [ 63 , 91 , 121 , 122 , 123 ], having a clear understanding of resistance mechanisms is of paramount importance ( Figure 2 ). Although modification of the drug target, ERG11 , is an important azole resistance mechanism in species belonging to CTG ( C .…”
Section: Mechanisms Of Antifungal Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Generally, changes in drug affinity at the drug target for azoles and echinocandins and overexpression of the drug target and efflux pumps are the major determinants of azole resistance. Considering that azoles are the main drug used to treat invasive candidiasis in developing countries [ 63 , 91 , 121 , 122 , 123 ], having a clear understanding of resistance mechanisms is of paramount importance ( Figure 2 ). Although modification of the drug target, ERG11 , is an important azole resistance mechanism in species belonging to CTG ( C .…”
Section: Mechanisms Of Antifungal Resistancementioning
confidence: 99%
“…tropicalis and C . parapsilosis isolates [ 47 , 118 , 122 , 134 , 135 , 136 ], which could serve as a basis to broaden our understanding of azole resistance mechanisms in C . parapsilosis and C .…”
Section: Mechanisms Of Antifungal Resistancementioning
confidence: 99%
“…The high rate of FLZR for a species that used to be susceptible to azoles may have arisen from the disproportionate use of azoles in the hospital [170,182]. The notable increase in the prevalence of FLZR C. parapsilosis isolates could be a major threat in developing countries, in which the vast majority of candidemia cases are treated with FLZ [138,169,182,186]. By contrast, according to the SENTRY study, echinocandin resistance is a rare phenomenon among C. parapsilosis isolates (up to 0.1%) [79].…”
Section: Candida Parapsilosismentioning
confidence: 99%
“…The notable increase in the prevalence of FLZR C . parapsilosis isolates could be a major threat in developing countries, in which the vast majority of candidemia cases are treated with FLZ [ 138 , 169 , 182 , 186 ]. By contrast, according to the SENTRY study, echinocandin resistance is a rare phenomenon among C .…”
Section: Epidemiology and Mechanisms Of Antifungal Resistance In Nmentioning
confidence: 99%
“…Surprisingly, new studies from Turkey [ 17 , 18 ] and South Korea [ 20 ] reported a substantial increase in prevalence of FLCR C. parapsilosis after 2015, which appeared partially due to the expanded use of azoles in clinical settings. Despite extremely low rates of echinocandin-resistant C. parapsilosis blood isolates [ 1 ], recent candidemia studies from Iran [ 21 ] and Turkey [ 22 ] have shown emerging multidrug-resistant (MDR) C. parapsilosis isolates resistant against both echinocandins and azoles. Of particular concern is the horizontal transfer of clonal FLCR and MDR C. parapsilosis to antifungal-naïve patients [ 18 , 22 ], which notoriously limit the efficacy of these two most widely used antifungals.…”
Section: Introductionmentioning
confidence: 99%